Abnormal improvement in emission of lanthanum oxysulfide phosphor La2O2S:Tb3+ synthesized by a novel method, thermal decomposition in eutectic molten salt. Issue 8 (June 2016) - Kim, Sun Woog; Hasegawa, Takuya; Abe, Takeshi; Nakagawa, Hiroko; Hasegawa, Shota; Seki, Kohei; Toda, Kenji; Uematsu, Kazuyoshi; Ishigaki, Tadashi; Sato, Mineo
Abstract: The lanthanum oxysulfide phosphor La2 O2 S:Tb 3+ is generally synthesized by the direct sulfidation of La2 O3 using H2 S or CS2 gas. However, these gases are known to be highly toxic to humans. In this paper, a new synthesis method that uses 0.6Li2 SO4 –0.4Na2 SO4 as the flux is proposed for obtaining La2 O2 S:Tb 3+ phosphor, without the need for H2 S or CS2 gas. The proposed method consists of two steps: 1) oxidation to obtain La2 O2 SO4 and 2) reduction to reduce La2 O2 SO4 to La2 O2 S. Using this novel method, (La1− x Tb x )2 O2 S (0.01≤ x ≤0.13) were successfully synthesized in a single-phase form. The synthesized phosphors exhibited extraordinary luminescence behavior. Further, despite their low Tb 3+ ion content, the phosphors showed high emission intensities. The relative emission intensity of (La0.95 Tb0.05 )2 O2 S ( λ ex =270 nm) was 132% that of the commercial green-emitting phosphor (La0.52 Ce0.31 Tb0.17 )PO4 ( λ ex =285 nm), which shows the highest excitation absorption.